Study of Aerodynamics Characteristics of Popular Sports Utility Vehicle in Indonesia - Julian, James James; Wahyuni, Fitri; Anggara, Rizki Aldi; Naufal, Ridwan Daris (Fakultas Teknik Universitas Muria Kudus, 2025)
The concept of aerodynamics is an essential aspect of designing a vehicle. In this study, the aerodynamic characteristics of the Sports Utility Vehicle (SUV) model are investigated using a numerical approach. This study uses three popular SUV models in Indonesia, including the Toyota Fortuner, Mitsubishi Pajero, and Hyundai Santa Fe. The three SUV models were tested at three different speed variations, including 20 km/h, 50 km/h, and 100 km/h. Based on the computational results, it was found that each SUV model produced a CD value that varied between 0.32 and 0.38. The highest CD value was obtained by the Toyota Fortuner, followed by two other vehicle models, including the Mitsubishi Pajero and Hyundai Santa Fe. The CD value obtained by each vehicle is dominated by drag pressure. This condition is indicated by the flow separation phenomenon, which causes a recirculation zone. In addition, the large frontal area causes an increase in stagnation pressure so that the pressure difference between the front and rear sides of the vehicle body causes significant drag. Based on the drag reduction percentage, the Hyundai Santa Fe Vehicle is the most aerodynamic vehicle model, with its ability to reduce drag by up to 6,604%. In addition, the Mitsubishi Pajero can reduce drag by up to 2,187%. On the other hand, the Toyota Fortuner cannot reduce drag because it has a CD value that is higher than the average CD value for SUV models.